2004
DOI: 10.1111/j.1538-7836.2004.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical criteria to prevent unnecessary diagnostic testing in emergency department patients with suspected pulmonary embolism

Abstract: To cite this article: Kline JA, Mitchell AM, Kabrhel C, Richman PB, Courtney DM. Clinical criteria to prevent unnecessary diagnostic testing in emergency department patients with suspected pulmonary embolism. J Thromb Haemost 2004; 2: 1247-55.See also Le Gal G, Bounameaux H. Diagnosing pulmonary embolism: running after the decreasing prevalence of cases among suspected patients.This issue, pp 1244-6; Linkins L.-A., Bates SM, Ginsberg JS, Kearon C. Use of different D-dimer levels to exclude venous thromboemboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
280
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(315 citation statements)
references
References 37 publications
4
280
1
8
Order By: Relevance
“…D-dimer is widely used clinically for the detection of in-vivo fibrin formation, and plasma levels of D-dimer are reported to be increased in patients with disseminated intravascular coagulation (DIC) [1,2], deep vein thrombosis (DVT)/pulmonary embolism (PE) [3][4][5][6], and acute myocardial infarction [7]. D-dimer has been adopted by the International Society of Thrombosis and Haemostasis as a diagnostic criterion of overt DIC [8].…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer is widely used clinically for the detection of in-vivo fibrin formation, and plasma levels of D-dimer are reported to be increased in patients with disseminated intravascular coagulation (DIC) [1,2], deep vein thrombosis (DVT)/pulmonary embolism (PE) [3][4][5][6], and acute myocardial infarction [7]. D-dimer has been adopted by the International Society of Thrombosis and Haemostasis as a diagnostic criterion of overt DIC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tachycardia is a component of both the Wells prediction rule and the PERC criteria. 24,25 However, obesity can cause significant tachycardia, and the heart rate increases in a linear fashion with the BMI. 26 A 1984 study showed that respiratory rates in normal resting obese patients (body weight greater than 190% of predicted ideal weight) are typically 40% higher than non-obese patients.…”
Section: Signs and Symptoms Of Pe In Obese Patientsmentioning
confidence: 99%
“…22 Obesity itself is not included as a component of any of the commonly used standardized clinical decision rules to determine the clinical probability of PE including the Geneva score, the Wells prediction rule, or the PERC criteria used in emergency rooms to determine the need for additional testing in patients with suspected PE. [23][24][25] Tachycardia and tachypnea are the two most common signs found in PE. Tachycardia is a component of both the Wells prediction rule and the PERC criteria.…”
Section: Signs and Symptoms Of Pe In Obese Patientsmentioning
confidence: 99%
“…If the clinical gestalt is that PE is unlikely and all of the following variables are present, further testing can be safely discontinued: (1) pulse <100; (2) age <50; (3) oxygen saturation (SaO 2 ) >94%; (4) no unilateral leg swelling; (5) no hemoptysis; (6) no recent trauma or surgery; (7) no prior DVT or PE; and (8) no hormone use. 13 In a large, multicenter study, these criteria combined with a gestalt interpretation of low risk were shown to select a subgroup of patients with a very low probability of PE (<2%).…”
mentioning
confidence: 99%
“…13 The PERC rule consists of 8 variables designed to offer a pretest probability of PE of less than 1.8%, a probability at which further testing is unnecessary. If the clinical gestalt is that PE is unlikely and all of the following variables are present, further testing can be safely discontinued: (1) pulse <100; (2) age <50; (3) oxygen saturation (SaO 2 ) >94%; (4) no unilateral leg swelling; (5) no hemoptysis; (6) no recent trauma or surgery; (7) no prior DVT or PE; and (8) no hormone use.…”
mentioning
confidence: 99%